2008
DOI: 10.1007/s12098-008-0143-1
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 and homocysteine status in asymptomatic Indian toddlers

Abstract: Low serum vitamin B(12) (V B(12)) and hyperhomocysteinemia have been reported in asymptomatic Asian Indian men. We studied the prevalence of V B(12) deficiency and hyperhomocysteinemia in 51 asymptomatic toddlers, from Pune, India. V B(12) levels were low and total serum homocysteine was high in 14% and homocysteine levels were significantly higher in boys. Programming for cardiovascular risk in adulthood possibly starts at a very young age through the homocysteine axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…In 51 urban toddlers in Pune, the prevalence of vitamin B-12 deficiency was 14% (36). These studies were conducted in urban populations, whereas, to our knowledge, our study was the first study conducted in a rural setting.…”
Section: Tablementioning
confidence: 78%
“…In 51 urban toddlers in Pune, the prevalence of vitamin B-12 deficiency was 14% (36). These studies were conducted in urban populations, whereas, to our knowledge, our study was the first study conducted in a rural setting.…”
Section: Tablementioning
confidence: 78%
“…Hanumante et al found that 14% of the asymptomatic toddlers with mean age of 2.4 years were cobalamin deficient. 31 This study attributed the deficiency to low intake of animal source foods and typical Indian vegetarian diet. In a recent community based cross sectional study on 470 Indian children aged 12 to 59 months, the prevalence of B12 deficiency was observed to be 38.4%, very similar to our findings.…”
Section: Discussionmentioning
confidence: 97%
“…The homocysteine levels were high, as expected. 23 Studies from many other third-world countries also indicate high prevalence of vitamin B12 deficiency in childhood. In a study from Turkey, 180 pregnant women and their term babies were sampled.…”
Section: Discussionmentioning
confidence: 99%